Review papersAge-dependent biomechanical properties of the skin - Pawlaczyk, Mariola; Lelonkiewicz, Monika; Wieczorowski, Michał (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
The skin fulfills one of its most important functions, that is protection from mechanical injuries, due to the mechanism of reversible deformation of the structure. Human skin is a complex living material but in biomechanical tests it reveals its homogeneous nature. Biomechanical skin parameters change with time. Results of thickness measurements, where the skin was subjected to pressure, revealed that the Young’s modulus increased linearly with age. The process of ageing is the reason why the skin becomes thinner, stiffer, less tense and less flexible. Skin tension measured during in vivo uniaxial load and the elasticity modulus are higher in children than in elderly adults. Furthermore, mean ultimate skin deformation before bursting is 75% for newborns and 60% for the elderly. Several types of the main lines were distinguished on the skin. The static lines, described by Langer, correspond to the lines of maximum tension, the Kraissl’s lines correspond to the movements of the skin during muscle work, whereas the Borges lines are the relaxed skin tension lines. Biomechanical tests of the human skin help to quantify the effectiveness of dermatological products, detect skin diseases, schedule and plan surgical and dermatological interventions and treatments.